Synthesis and Pharmacological Significance of Isoxazoline Derivatives: A Mini review - mohammed alwan (Academic Science Journal)
Five-membered heterocycles, like isoxazolines, are an important class of compounds of bioorganic and pharmacological importance. They have been treated as useful intermediates for the transformation of a large number of bioactive molecules.